Optimizing Education: A Mixed Methods Approach Oriented to Teaching Personal and Social Responsibility (TPSR) - Camerino, Oleguer; Valero-Valenzuela, Alfonso; Prat, Queralt; Manzano Sánchez, David; Castañer, Marta (Frontiers in Psychology, 2019)
This methodological article provides a Mixed Method approach to analyze how the Teaching Personal and Social Responsibility (TPSR) Model is feasible to enhance student’s autonomy. The objective is to detect how teachers’ behavior-oriented patterns shift in response to continuing professional development to reinforce TPSR strategies. We compared the application of TPSR by three teachers who had previously attended a training course for this model, with that of an expert in the model. A total of 44 sessions of primary and secondary school semesters in various subjects, taught by all four teachers and comprising 120 students. A mixed-method approach followed in the study involved: (a) the Observational System of Teaching Oriented Responsibility (OSTOR), which revealed how the teachers’ behavior patterns shifted over their interventions, and (b) the Tool for Assessing Responsibility-Based Education (TARE 2.0.), which focused on perceived behaviors by teachers and student behaviors. Data analysis was conducted for (a) the T-pattern detection technique, (b) polar coordinate analysis to obtain detailed sequences of instruction, and (c) descriptive and correlational analysis from the TARE. The mixed-method analysis of data confirms how the TPSR improved the teaching behaviors of the three teachers in training compared with the expert teacher.